Steric blocking upside down: a different way of thinking about the competition between myosin and tropomyosin - Chalovich, Joseph M. (Frontiers in Physics, 2024)
At low free Ca 2+ , the actin binding proteins tropomyosin, troponin I, troponin T and troponin C inhibit contraction in striated muscles. Ca 2+ activation alters the position of tropomyosin on actin to uncover binding sites for high affinity forms of myosin (i.e. myosin-ADP). Inhibition of contraction is commonly thought to result from steric blocking of myosin binding to actin by tropomyosin. However, myosin-ADP binding to actin is energetically more favorable than localization of tropomyosin in the blocking position. Tropomyosin is an effective inhibitor of binding only at low levels of myosin-ADP. At low free Ca 2+ , troponin-tropomyosin also inhibits the rate of a step associated with Pi release to about 1% of the maximum rate. This results in accumulation of myosin with bound ATP and ADP-Pi. Such myosin binds weakly to actin. Ca 2+ activation increases the rate of Pi release, but not to the maximum value, and increases the population of myosin-ADP. The high affinity binding of myosin-ADP to actin can displace tropomyosin into the fully active position in relation to the amount of myosin-ADP bound. It seems likely that an important outcome of the steric clash between myosin-ADP and tropomyosin is the is dual activation by Ca 2+ and myosin-ADP. The C-terminal region of troponin T (TnT) contributes to the incomplete activation by Ca 2+ alone. Because this region of TnT is highly conserved, the ability of myosin-ADP to move tropomyosin may be more important than any restriction that tropomyosin may place on myosin binding.